PENGUKURAN DAN PENILAIAN RANAH AFEKTIF DALAM PENDIDIKAN JASMANI - Suwito, Ngatman (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 79.4pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 240.7pt; mso-height-rule: exactly;">Abstract <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Physical education programs designed and <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">implemented from preschool to post secondary level <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">are principally for achieving the goals of physical <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">education consist of four aspects. Those aspects are <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">cognitive, psychomotor, affective, and physical <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">domains. The measurement and evaluation of <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">affective domain, like other domains, can be done <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">through physical education teaching programs. The <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">psychological development in the affective domain <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">context such as attitude, behavior, interest, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">sportsmanship, leadership, social behavior, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">personality can be measured. Although these <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">psychological features have been seen as side <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">impacts, they become the main purpose in teaching <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">physical education which eventually helps character <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">building. Some instruments that can be used to <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">measure and evaluate affective domain have been <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">constructed to measure those psychological features. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">They are attitude, behavior, interest, sportsmanship, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">leadership, social behavior, personality inventory. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">There are also some established methods and types <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">of scale such as quantitative methods (Likert Scale), <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">semantic differential scale, serial level scale) and <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.75pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">qualitative methods (interview and observation). <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 603.7pt; mso-height-rule: exactly;">Kata kunci: Pengukuran, Penilaian, Ranah Afektif, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 603.7pt; mso-height-rule: exactly;">Pendidikan Jasmani.